Determinants of Mortality in Epithelial Ovarian Cancer: Systematic Review and Meta-analysis (Last 5 Years) - Fitriyadi Kusuma; Kemal Akbar Suryoadji; Nadia Ayu Mulansari; Garry Soloan; Kieran Pasha Ivan Sini; Anisa Saphira Wulandari; Vira Nur Arifa; Marshaly Safira Masrie; Fahrayhansyah Muhammad Faqih; Bintang Wirawan (Journal of Applied Holistic Nursing Science, 2026)
ABSTRACT Background: Ovarian cancer, ranking third among gynecologic cancers, poses a significant global health challenge. Despite affecting over 239,000 annually and causing 150,000 deaths, the overall survival rate is 45.6%. Variability in survival rates across different stages necessitates a detailed understanding of contributing factors. This systematic review and meta-analysis explores recent research to illuminate crucial aspects influencing epithelial ovarian cancer (EOC) patient outcomes. Methods: A protocol registered in PROSPERO (ID: CRD42024502616) guided this systematic review, focusing on cohort studies examining prognostic factors for EOC mortality. Eligibility criteria included relevance to mortality risk, clear extraction methods, and English language. A PRISMA-guided search with the keywords “((Ovarian Cancer) AND (Mortality) AND (Risk)” across Scopus, PubMed, and Cochrane. Evaluation of 66,191 samples from 16 cohort studies identified several key prognostic factors for mortality in epithelial ovarian cancer (EOC). Results: Advanced FIGO stage (III-IV) and high-grade serous histology were significant predictors of higher mortality, with stage III-IV showing a risk ratio of 3.62 (95% CI 3.35–3.91). Older age, greater inflammation (higher BMI, smoking), and bilateral tumors also increased mortality risk. Additionally, lifestyle factors like reduced physical activity and rural living, as well as treatment-related factors such as perioperative red blood cell transfusion, were associated with poorer survival outcomes. This systematic review provides comprehensive insights into the complex landscape of EOC survival. Key prognostic factors for mortality in EOC patients include advanced cancer stage, high-grade serous histology, older age, inflammation, and bilateral tumors. Treatment factors such as perioperative transfusion and neoadjuvant chemotherapy intensity also play a critical role. Conclusion: These findings highlight the need for personalized treatment strategies based on these factors to improve survival outcomes for EOC patients.